2018
DOI: 10.1038/s41467-018-04887-1
|View full text |Cite
|
Sign up to set email alerts
|

High-veracity functional imaging in scanning probe microscopy via Graph-Bootstrapping

Abstract: The key objective of scanning probe microscopy (SPM) techniques is the optimal representation of the nanoscale surface structure and functionality inferred from the dynamics of the cantilever. This is particularly pertinent today, as the SPM community has seen a rapidly growing trend towards simultaneous capture of multiple imaging channels and complex modes of operation involving high-dimensional information-rich datasets, bringing forward the challenges of visualization and analysis, particularly for cases w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 73 publications
0
16
0
Order By: Relevance
“…The primary tuning parameter of HDBSCAN is the minimum cluster size k. We follow a similar procedure in Ref 29 to choose k. We first consider all integer k values in the range [20,149]. In supplementary Figure 2, we then plot the trend of total number of estimated clusters against every k value and fit this trend by the exponential decay.…”
Section: Manifold Clusteringmentioning
confidence: 99%
“…The primary tuning parameter of HDBSCAN is the minimum cluster size k. We follow a similar procedure in Ref 29 to choose k. We first consider all integer k values in the range [20,149]. In supplementary Figure 2, we then plot the trend of total number of estimated clusters against every k value and fit this trend by the exponential decay.…”
Section: Manifold Clusteringmentioning
confidence: 99%
“…Clustering can be subsequently performed on the lowdimensional manifold to underpin the intrinsic structure within the manifold that corresponds to the material structure heterogeneity. To better partition intrinsic manifold clusters (facilitating clustering tasks), Li et al recently proposed a Graph-Bootstrapping procedure 25,26 that iteratively reconstructed the NN graph based on previous manifold positions and then recalculated manifold coordinates based on the reconstructed NN graph. The projected low dimensional manifold clusters represent featured spectral property of the materials, thereby allowing for gaining insights of latent material structures via external validations such as rst principle theories.…”
Section: Resultsmentioning
confidence: 99%
“…Low-dimensional manifold embedding for TERS measurements is calculated via a modi ed Graph-Bootstrapping approach. 25,26 Graph-Bootstrapping is an iterative procedure that consists of two main steps: construction of nearest neighbor graph and manifold layout of nearest neighbor graph. During the initialization (iteration 0) of Graph-Bootstrapping, a nearest neighbor graph is calculated based on the high-dimensional TERS measurements, which we call this graph as root graph.…”
Section: Manifold Clusteringmentioning
confidence: 99%
See 1 more Smart Citation
“…Manifold learning has been applied in many fields including text mining, social network visualization, and so on. In the domain of microscopy imaging, Li et al reported functional imaging and mapping of AFM images and 4D‐STEM data based on manifold learning, and 10 types of Ronchigrams from experimental 4D‐STEM data of monolayer graphene doped with Si were identified. The clusters in the low dimensional space exhibit improved separability after a graph‐bootstrapping process .…”
Section: Structure Representation Via Dimension Reductionmentioning
confidence: 99%